[PP.29.35] PREDICTORS OF FUNCTIONAL OUTCOME IN LACUNAR STROKE. (September 2017) - Alonzo, C.; Brescacín, L.; Zurrú, M.; Guido, B.; Baroni, M.; Luzzi, A.; Cámera, L.; Waisman, G.
Abstract : Objective: Lacunar infarcts are small deep infarcts caused by occlusion of the penetrating branches of the major cerebral arteries, and are strongly related with chronic hypertension and its control. As microangiopatic disease burden correlates with poor functionality, we aimed to evaluate predictors of bad functional outcome in patients with lacunar stroke. Design and method: Consecutive patients with lacunar stroke were included in the analysis. Demographic data and pre-stroke vascular risk factor (VRF) profile and control were collected from electronic records. Disability (modified Rankin scale) was evaluated one month after the event and analyzed in two groups: 1) bad oucome (m-Rankin > 1) and 2) good outcome (m-Rankin 0–1). Results: We analyzed data of the 309 lacunar strokes between December 2006 and December 2015, 32% (n 99) had bad outcome. These patients were older (78 ± 9 vs 73 ± 10, p 0.0002) with no differences in VRF profile and control between groups. Patients with bad outcome were more likely to have impaired e-GFR (58% vs 38%, p 0.002) and atrial fibrillation (6% vs 1%, 0.007), as well as higher post-stroke hs-CRP (>3 mg/L), 45% vs 10%, p 0.0001. They also had higher incidence of resistant hypertension (3 o more drugs including a diuretic) before stroke (61% vs 14%, p 0.0001). Predictors of bad outcome in the multivariate analysis are shown in the table. Figure. No caption available. Conclusions: As expected, older patients and those with resistant hypertension had worse outcome after stroke but it is noticeable that, in our cohort, an inflammatory marker related with endothelial dysfunction and a surrogate marker of renal microangiopathy were also predictors of bad functional outcome.